2019
DOI: 10.1186/s13017-019-0227-4
|View full text |Cite
|
Sign up to set email alerts
|

Open conversion for laparoscopically difficult cholecystectomy is still a valid solution with unsolved aspects

Abstract: The difficult laparoscopic cholecystectomy remains a surgical challenge for surgeons who must decide between laparoscopic continuation and open conversion. The balance between the lack of open surgery training of young surgeons and the risk of maintaining the laparoscopic approach in difficult laparoscopic cholecystectomy is still an unresolved problem. Furthermore, the time that must be spent in an attempt to complete laparoscopic surgery before conversion is still controversial. The authors in this letter di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The experience of surgeons has a crucial role in determining the need and justification for conversion. 20,21 In our study, it was found out by the surgical team that the operation was completed by conversion approximately in 53% of the entire partial cholecystectomy cases. In 47% of the cases, the procedure was completed as LPC.…”
Section: Complicationsmentioning
confidence: 68%
“…The experience of surgeons has a crucial role in determining the need and justification for conversion. 20,21 In our study, it was found out by the surgical team that the operation was completed by conversion approximately in 53% of the entire partial cholecystectomy cases. In 47% of the cases, the procedure was completed as LPC.…”
Section: Complicationsmentioning
confidence: 68%
“…The present update of the WSES Guidelines on ACC clarifies that, in 2016, the reasons for conversion were used as a proxy in the absence of high-quality studies; we maintained the same approach for the current version of the guidelines [7,101,102].…”
Section: Patients Who Are Pregnantmentioning
confidence: 99%
“…The absence of the critical view of safety (CVS) is the most important factor for conversion to open surgery. Mandatory indicators for conversion include a complete buried gallbladder, an impacted stone and the inability to retract the gallbladder [ 42 ]. In cases of severe inflammation, the identification and the dissection of the Calot’s triangle could be difficult.…”
Section: Acute Cholecystitismentioning
confidence: 99%